Creative and innovative ways of Islamic da’wah: lessons drawn from the seerah nabawiyyah - Abdullah @ Chuah Hock Leng, Osman (2014)
Prophet Muhammad was the most creative and innovative man in delivering the message of Allah to his followers. History has proven that his wisdom and innovative method in communicating to people was able to transform the ignorant and uncultured Arabs of his time into highly civilized people within decades after his demise. Taking into account of the great success made by the Prophet of Islam in the field of Da’wah, this paper intends to explore and investigate in a comparative manner the methodologies used by him and the earlier prophets, who were his predecessors. Since Islam and Muslims exist all over the world, this paper would also examine how lessons drawn out from Seerah Nabawiyyah can be put to good use in modern day Da’wah